2013
DOI: 10.1007/s00784-013-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotics in periodontal diseases: a systematic review

Abstract: The use of probiotics are described to prevent or treat periodontal diseases in some clinical trials; therefore, a systematic review of the evidence for the effect of periodontal diseases is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 13 publications
0
34
0
1
Order By: Relevance
“…Several in vitro studies (Teughels et al, 2007; van Essche et al, 2012) and recent clinical studies (Iniesta et al, 2012; Teughels et al, 2013; Yanine et al, 2013) have suggested that these allegedly beneficial bacteria can cause antagonism toward Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies (Teughels et al, 2007; van Essche et al, 2012) and recent clinical studies (Iniesta et al, 2012; Teughels et al, 2013; Yanine et al, 2013) have suggested that these allegedly beneficial bacteria can cause antagonism toward Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that probiotics could be beneficial during periodontal therapy because they may aid in the reduction of pathogenic bacteria 14 and/or serve as anti‐inflammatory adjuncts 15 , 26 . However, a recent review concludes that more studies are necessary to evaluate the efficacy of probiotics in oral health maintenance 27 and to understand the mechanisms by which ingested bacteria target microbiome functions contributing to the prevention and management of major health concerns 28 . This study proposes that a treatment involving non‐surgical therapy plus intake of a L. rhamnosus SP1‐containing probiotic sachet may result in improved clinical effects compared with conventional mechanical therapy for CP.…”
mentioning
confidence: 99%
“…Several clinical trials were conducted in order to study the effect of administration of probiotics in initial treatment of periodontitis [114][115][116][117]. The bacteria most frequently used as probiotic are L. reuteri (DSM 17938 + ATCC PTA 5289) [72,[118][119][120], Lactibacillus salivarius WB21 [121,122], L. reuteri (ATCC 55730 + ATCC PTA 5289) [123], L. reuteri (ATCC PTA 5289) [61], Streptoccus oralis KJ3 + Streptococcus uberis KJ2 + Streptoccus rattus JH145 [124] and L. rhamnosus SP1 [125].…”
Section: Probiotics and Periodontitismentioning
confidence: 99%